Brokers of crisis: the everyday uncertainty of Eastern Congo's mineral négociants*. Issue 4 (23rd November 2017) - Vogel, Christoph; Musamba, Josaphat
ABSTRACT: Eastern Democratic Republic of the Congo's (DRC) artisanal mining sector is often linked to the violent conflicts that have beset Central Africa for over two decades. While many analyses emphasise its 'criminal' and 'illegal' nature, less attention has been paid to the ambiguity of this economy, most prominently incarnated by the intermediate mineral traders called négociants . Focusing on their entrepreneurship, networks and everyday activities, this essay offers a more nuanced understanding of local mineral trade in the context of a 'crisis economy' framed by competing governable orders. It investigates the uncertainty along eastern DRC's mineral supply chains, that are undergoing major regulatory changes to curb the trade of so-called 'conflict minerals'. Drawing from extensive fieldwork, this essay demonstrates how this uncertainty shapes the négociants' role as brokers of socio-economic life in the provinces of North and South Kivu.